Overview of Online Friendships Among Vocational High School Students - Tae, Philomena Firmina; Lerik, Mariana Dinah Ch.; Wijaya, R. Pasifikus Christa (Universitas Nusa Cendana, 2025)
This study aims to describe online friendships among vocational high school (SMK) students in Kupang City. The research employed a quantitative descriptive approach involving 362 students from five public and private vocational schools in Kupang City. The instrument used was the Online Friendship Scale developed by Helmi, Widhiarso, and Husna (2017), which includes four aspects: sharing, voluntariness, companionship, and mutual support. The results indicate that adolescents are fairly active in engaging in online peer interactions; however, the intensity, closeness, and social support developed through these interactions have not yet reached an optimal level. The aspects of sharing and voluntariness reflected good openness and willingness, while companionship and mutual support were at high levels, indicating the presence of positive social support in digital media. These findings highlight the importance of digital literacy and character guidance to strengthen adolescents’ social relationships in a healthy and meaningful way.